Nafion membranes with a porous surface - Quoc Khanh Dang; Henkensmeier, Dirk; Krishnan, N. Nambi; Jang, Jong Hyun; Kim, Hyoung-Juhn; Nam, Suk Woo; Lim, Tae-Hoon (Elsevier BV, 2014)
Nation membranes with a monolayer of pores on one surface (P-Nation) were prepared by casting a Nation SE20092 dispersion containing ortho-dichlorobenzene. The pores are not connected but provide 2 mu m large openings, increasing the membrane surface by one dimension. The thickness of the porous layer is typically < 5 mu m. In catalyst coated membranes the catalyst layer penetrated the pores well The effect on the performance of a polymer electrolyte fuel cell (PEFC) was investigated at 95 degrees C. The porous layer formed the cathode, to enhance water back diffusion. After 24 h equilibration, 30-35 mu m thick P-Nafion gave 10-16% higher current density, reaching 858 mA/cm(2) at 0.4 V and 50% rh. N211 and P-Nafion equilibrated for 8 min showed peak power densities of 56 and 208 mW/cm(2) under anhydrous conditions, respectively, indicating that drying processes are slowed down. The stability of a MEA was tested for 240 h at 0.4 V and 50% rh (anode/cathode), without observable degradation. Under fully humidified conditions, the electrochemical surface area (ECSA) increased 40% in comparison to a N211 based MEA. At 65 degrees C, the ECSA more than doubled, showing 141 m(2)/g Pt. Also influence of the pores on water transport through a membrane and stability against membrane electrode delamination were considered. (C) 2014 Elsevier B.V. All rights reserved,